Wewnętrzne Momenty w Ciałach Stałych i Kontinuum ze Strukturą Wewnętrzną - Morandi, B. (Engineering Transactions, 1966)
This paper is a survey of works published until 1964 about couple-stresses, not considered by the classical theory of elasticity, and the capability of the latter to describe motions connected with the atomistic structure of matter. Since the re-discovery of the French scientists, E. and F. COSSERAT both the problems have been unified in the study of new and more elaborate mathematical models of a continuum with an "internal structure", involving in turn a new accurate survey of fundamental principles of mechanics of continua.